Tension pneumothorax during peroral endoscopic myotomy for treatment of esophageal achalasia under general anesthesia - Li,Tsung-Shih (2017)
Abstract More and more endoscopically gastrointestinal procedures require anesthesiologists to perform general anesthesia, such as "peroral endoscopic myotomy". Peroral endoscopic myotomy is a novel invasive treatment for the primary motility disorder of esophagus, called esophageal achalasia. Despite of its minimally invasive feature, there are still complications during the procedure which develop to critical conditions and threat patients’ lives. Herein we describe a case about tension pneumothorax subsequent to esophageal rupture during peroral endoscopic myotomy. The emergent management of the complication is stated in detail. The pivotal points of general anesthesia for patients undergoing peroral endoscopic myotomy are emphasized and discussed. Also, intraoperative and post-operative complications mentioned by literature are integrated.